2018
DOI: 10.1038/s41598-018-33662-x
|View full text |Cite
|
Sign up to set email alerts
|

Candidemia due to uncommon Candida species in children: new threat and impacts on outcomes

Abstract: Many uncommon Candida spp. (species other than C. albicans, C. parapsilosis, C. glabrata, C. tropicalis, and C. krusei) have been shown to emerge in tertiary care facilities. We aimed to investigate these uncommon candidemia in children. Forty-six cases of candidemia caused by uncommon Candida spp. were identified during 2003–2015 from a medical center in Taiwan. The most common specie was C. guilliermondii (31.2%), followed by C. lusitaniae (18.8%) and C. metapsilosis (18.8%). These cases were analyzed and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 50 publications
1
20
1
2
Order By: Relevance
“…However, similar to other studies, we here observed that C. albicans was the predominant Candida species responsible for candidaemia, and the incidence of candidaemia associated with C albicans vs that associated with non-albicans Candida species was almost the same (49% vs 51%, respectively). 7,13,14,22 In the current study, we observed signifi- Candida tropicalis was the third most frequent causal agent of candidaemia, responsible for 18.18% mortality in patients examined in this study. Candida tropicalis appears to be more virulent than C. albicans and is more prone to causing invasive candidiasis with a high rate of mortality than the latter.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…However, similar to other studies, we here observed that C. albicans was the predominant Candida species responsible for candidaemia, and the incidence of candidaemia associated with C albicans vs that associated with non-albicans Candida species was almost the same (49% vs 51%, respectively). 7,13,14,22 In the current study, we observed signifi- Candida tropicalis was the third most frequent causal agent of candidaemia, responsible for 18.18% mortality in patients examined in this study. Candida tropicalis appears to be more virulent than C. albicans and is more prone to causing invasive candidiasis with a high rate of mortality than the latter.…”
Section: Discussionsupporting
confidence: 50%
“…Strikingly, invasive candidiasis caused by non‐ albicans Candida species has only been reported in the past two decades . Non‐ albicans Candida species have emerged as agents of candidaemia, with an overall decreased incidence rate of C. albicans from 70% to 50% in developed countries.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations